Oxidative stress in microorganisms--I. Microbial vs. higher cells--damage and defenses in relation to cell aging and death - Sigler, K; Chaloupka, J; Brozmanová, J; Stadler, N; Höfer, M (Folia microbiologica, 1999)
Oxidative stress in microbial cells shares many similarities with other cell types but it has its specific features which may differ in prokaryotic and eukaryotic cells. We survey here the properties and actions of primary sources of oxidative stress, the role of transition metals in oxidative stress and cell protective machinery of microbial cells, and compare them with analogous features of other cell types. Other features to be compared are the action of Reactive Oxygen Species (ROS) on cell constituents, secondary lipid- or protein-based radicals and other stress products. Repair of oxidative injury by microorganisms and proteolytic removal of irreparable cell constituents are briefly described. Oxidative damage of aerobically growing microbial cells by endogenously formed ROS mostly does not induce changes similar to the aging of multiplying mammalian cells. Rapid growth of bacteria and yeast prevents accumulation of impaired macromolecules which are repaired, diluted or eliminated. During growth some simple fungi, such as yeast or Podospora spp., exhibit aging whose primary cause seems to be fragmentation of the nucleolus or impairment of mitochondrial DNA integrity. Yeast cell aging seems to be accelerated by endogenous oxidative stress. Unlike most growing microbial cells, stationary-phase cells gradually lose their viability because of a continuous oxidative stress, in spite of an increased synthesis of antioxidant enzymes. Unlike in most microorganisms, in plant and animal cells a severe oxidative stress induces a specific programmed death pathway--apoptosis. The scant data on the microbial death mechanisms induced by oxidative stress indicate that in bacteria cell death can result from activation of autolytic enzymes (similarly to the programmed mother-cell death at the end of bacillary sporulation). Yeast and other simple eukaryotes contain components of a proapoptotic pathway which are silent under normal conditions but can be activated by oxidative stress or by manifestation of mammalian death genes, such as bak or bax. Other aspects, such as regulation of oxidative-stress response, role of defense enzymes and their control, acquisition of stress tolerance, stress signaling and its role in stress response, as well as cross-talk between different stress factors, will be the subject of a subsequent review.
Keywords: stárnutí buněk; Plants; Fungi; oxidační stres; antioxidancia; poškození DNA; DNA Damage; reaktivní formy kyslíku; Bacteria; Cell Death; houby; buněčná smrt; Microbiology; Cellular Senescence; metabolismus lipidů; Models, Biological; rostliny; Reactive Oxygen Species; Animals; kovy; mikrobiologie; biologické modely; Antioxidants; zvířata; Lipid Metabolism; Metals; Oxidative Stress